The RyR2-R2474S Mutation Sensitizes Cardiomyocytes and Hearts to Catecholaminergic Stress-Induced Oxidation of the Mitochondrial Glutathione Pool - Wegener, Jörg W.; Wagdi, Ahmed; Wagner, Eva; Katschinski, Dörthe M.; Hasenfuss, Gerd; Bruegmann, Tobias; Lehnart, Stephan E. (Frontiers in Physiology, 2021)
Missense mutations in the cardiac ryanodine receptor type 2 (RyR2) characteristically cause catecholaminergic arrhythmias. Reminiscent of the phenotype in patients, RyR2-R2474S knockin mice develop exercise-induced ventricular tachyarrhythmias. In cardiomyocytes, increased mitochondrial matrix Ca2+ uptake was recently linked to nonlinearly enhanced ATP synthesis with important implications for cardiac redox metabolism. We hypothesize that catecholaminergic stimulation and contractile activity amplify mitochondrial oxidation pathologically in RyR2-R2474S cardiomyocytes. To investigate this question, we generated double transgenic RyR2-R2474S mice expressing a mitochondria-restricted fluorescent biosensor to monitor the glutathione redox potential (EGSH). Electrical field pacing-evoked RyR2-WT and RyR2-R2474S cardiomyocyte contractions resulted in a small but significant baseline EGSH increase. Importantly, β-adrenergic stimulation resulted in excessive EGSH oxidization of the mitochondrial matrix in RyR2-R2474S cardiomyocytes compared to baseline and RyR2-WT control. Physiologically β-adrenergic stimulation significantly increased mitochondrial EGSH further in intact beating RyR2-R2474S but not in RyR2-WT control Langendorff perfused hearts. Finally, this catecholaminergic EGSH increase was significantly attenuated following treatment with the RyR2 channel blocker dantrolene. Together, catecholaminergic stimulation and increased diastolic Ca2+ leak induce an excessive, but dantrolene-inhibited mitochondrial EGSH oxidization in RyR2-R2474S cardiomyocytes.